The distributional effects of contractual norms: The case of cropshare agreements - Mary A. Burke (Federal Reserve Bank of Boston, 2015)
Share contracts are common in principal-agent relationships when returns are uncertain and it is costly to measure the agent's contribution. Well-known examples of these types of arrangements include sales commissions for real estate agents, contingency fees for attorneys, and cropshare contracts used in agriculture. An empirical feature of these contracts is that the shares specified are often based on focal points or historical norms, and seem excessively uniform given large and observable differences among the contracting parties. Using extensive survey data on cropshare contracts in Illinois, I test the hypothesis that contractual norms have measurable effects on factor returns. I find that tenants on higher-quality farmland capture a sizable portion of the land rent, controlling for nonlabor inputs, differences in labor quality, assortative matching effects, and riskiness in returns. Because the existence of a contractual norm is a valuable form of social capital for the bargaining parties, I argue that these distributional effects do not necessarily imply economic inefficiency.
Keywords: D01; D02; D33; Q15; 330; norms; share contracts; conformity; focal points